Debt in Low-Income Countries : Evolution, Implications, and Remedies - Essl, Sebastian; Kilic Celik, Sinem; Kirby, Patrick; Proite, Andre (World Bank, Washington, DC, 2019)
Debt vulnerabilities in low-income countries have increased substantially in recent years. Since 2013, median government debt has risen by about 20 percentage points of gross domestic product and increasingly comes from non-concessional and private sources. As a result, in most low-income countries, interest payments are absorbing an increasing proportion of government revenues. The majority of low-income countries would be hard hit by a sudden weakening in trade or global financial conditions given high levels of external debt, lack of fiscal space, low foreign currency reserves, and undiversified exports. A proactive effort to identify and reduce debt-related vulnerabilities is a priority for many low-income countries. Policy makers should focus on mobilizing domestic resources, improving debt transparency, and strengthening debt management practices. These efforts should be complemented by measures to strengthen fiscal frameworks, improve the efficiency of public expenditures and public investment management, and develop domestic financial systems.